STUDY OF THE INCIDENCE OF DISEASES AMONG PRIVATE AND PUBLIC SCHOOL STUDENTS RESULTS ANALYSIS (World Conference on Social Sciences, Law and Public Policy, 2026)
Maintaining the health of children, especially school-age children, is a priority for all countries. In order to raise and raise a healthy generation, it is of great importance to study the incidence of diseases among children. The results of the conducted studies show that chronic diseases such as asthma, epilepsy, and hypertension are widespread among school-age children. The prevalence of diseases among children varies depending on the geographical location of the country and the socio-hygienic status of the population.
Keywords: health indicators , especially school, morbidity, schoolchildren